PENGOPTIMALAN PENANGANAN SIMPANG EMPAT DI KAWASAN BUNDARAN KECIL: STUDI KASUS BUNDARAN KECIL KOTA PALANGKA RAYA - Cheria Yuliyesty (Lambung Mangkurat University Press, 2019)
Bundaran Kecil area in Palangka Raya is a very strategic and historic area on the road network in Palangka Raya City. Intersection in the area of ​​the Bundaran Kecil is a level intersection that has an asymmetrical axis and is equipped with traffic lights. Many intersections in urban areas are often not well planned, especially with regard to traffic lights and the geometry which makes control of vehicles difficult. The purpose of this research is to find out performance optimization and provide alternative solutions for handling intersections in the Bundaran Kecil area by using the Indonesian Road Capacity Manual (MKJI) for the present and the next 5 years. The results of existing conditions for the present study indicate that the value of the degree of saturation is above 1 with the level of service F. This shows that the intersection in the Bundaran Kecil requires a traffic management and signal cycle modification. The results of the analysis of several modifications obtained the best solution for the present time is a two-phase signal cycle with a degree of saturation of 0.4493. And after modifying the signal cycle, the best solution for the next 5 years is a 2-phase signal cycle with a degree of saturation of 0.7523.